2012
DOI: 10.1128/aac.00919-12
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mutations in Hepatitis C Virus NS5A Domain II Are Required To Confer a Significant Level of Resistance to Alisporivir

Abstract: Alisporivir is the most advanced host-targeting antiviral cyclophilin (Cyp) inhibitor in phase III studies and has demonstrated a great deal of promise in decreasing hepatitis C virus (HCV) viremia in infected patients. In an attempt to further elucidate the mechanism of action of alisporivir, HCV replicons resistant to the drug were selected. Interestingly, mutations constantly arose in domain II of NS5A. To demonstrate that these mutations are responsible for drug resistance, they were reintroduced into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 55 publications
5
51
0
Order By: Relevance
“…This is consistent with the fact that CypI have a unique MoA, which is the prevention of contacts between the host protein CypA and the viral protein NS5A [38,[43][44][45][46][47][51][52][53]. We showed that CypI such as ALV and SCY-635 block interactions between CypA and NS5A derived from various GTs [43][44].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This is consistent with the fact that CypI have a unique MoA, which is the prevention of contacts between the host protein CypA and the viral protein NS5A [38,[43][44][45][46][47][51][52][53]. We showed that CypI such as ALV and SCY-635 block interactions between CypA and NS5A derived from various GTs [43][44].…”
Section: Discussionsupporting
confidence: 65%
“…Two mutations-D320E and Y321N -were identified in the NS5A region of the STG-175-resistant replicon colonies. The D320E and Y321N mutations have been previously identified in HCV variants resistant to other CypI including CsA, ALV, SCY-635 and NIM811 [43][44][45][46][47][48][49]. Thus, it is likely that the double E320/N321 substitutions represent a common motif of partial resistance to CypI including STG-175.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting a cellular process also has the potential advantage of presenting a higher barrier for the development of resistance, a concept with substantial experimental and clinical support. For example, alisporivir (Debio 025) is another HCV inhibitor in advanced clinical development that targets host cyclophilin A, where the emergence of resistance is low and requires multiple viral mutations (59)(60)(61). However, cell-targeted antiviral compounds also have potential disadvantages, including toxicity and the potential for limited in vivo activity due to the redundancy of physiologic systems, such as exogenous dietary pyrimidine uptake mitigating the antiviral activity of dihydroorotate dehydrogenase inhibitors in mice (51).…”
Section: Discussionmentioning
confidence: 99%
“…The most advanced congeners are alisporivir (or DEB025) (7) and SCY-635 (8) 116 . Although virus mutations that confer resistance to alisporivir have been reported 109,110 , a synergistic effect when used in combination with anti-HCV DAAs has been noted 156 and the drug is in clinical trials for the treatment of HCV infection 69 . Additional in vivo studies with other relevant viruses will determine whether cyclophilin inhibitors will be of broad applicability.…”
Section: Bsas Derived From Fungi: Cyclosporine Statins and Mycophenomentioning
confidence: 99%
“…CypA interacts with viral proteins supporting viral replication 69 . CypA inhibitors such as cyclosporine A (CsA) have been shown to inhibit the replication of HIV, HCV, influenza virus, CoV, HBV, HSV, human cytomegalovirus (HCMV), VSV, vaccinia virus (VV) and human papillomavirus (HPV) [105][106][107][108][109][110][111][112][113][114] . Alisporivir (Debio-025) and SCY-635, both CsA analogues, have shown antiviral activity against HCV in vivo and are currently in combination with other anti-HCV compounds in various clinical trials 115,116 .…”
Section: Targeting Common Host-factors Used For Viral Replicationmentioning
confidence: 99%